Alcohol use disorder in patients with emergency application - Şengül, Cem; Serinken, Mustafa; Balcı Şengül, Ceyhan; Yüksel, Aykut; Aydın, Berrin (Journal of Dependence, 2010)
Objective: Alcohol using disorders was one of the most concerning problems for emergency department staff. Valid and reliable screening tests were needed for better diagnosis of alcohol related problems. In this study we aimed to investigate the emergency application of people with alcohol using disorders. Methods: We screened the alcohol using disorders with CAGE and AUDIT questionnaires. Data were evaluated with SPSS 11.0 software. Results: Total of 574 patients was evaluated with CAGE and AUDIT questionnaires. 39 <%6,8) patients were under risk of alcohol dependence with CAGE questionnaire and 40 (%7,0) with AUDIT questionnaire. Gender and psychiatric illness history were important markers for alcohol using disorder. Conclusion: Stating alcohol using disorders was possible with easy applicable screening tests like CAGE and AUDIT in emergency setting. Also using these instruments would give us better understanding and treatment chance of patients with alcohol using disorders in emergency setting.